Corporate Governance and Firm Value: Examining the Role of Board Age, Education, and Foreign Nationality - Rahman, Abdul (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study aims to examine the impact of board age, educational background, and foreign nationality on the firm value of mining companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022, from a corporate governance perspective. A quantitative approach with associative research methodology is employed, utilizing eViews version 12 and multiple linear regression analysis for data measurement. The research population comprises mining companies listed on the IDX during the specified period. The sample is determined using purposive sampling, resulting in a total of 18 companies and 72 observations. Secondary data is used in this study, obtained from the official IDX website (www.idx.co.id). Hypothesis testing is conducted using the t-test (partial) and R-test. The findings indicate that the age of board members significantly influences firm value, whereas the educational background of directors and the presence of foreign nationals on the board do not have a significant impact. The study concludes that the number of board members holding degrees in economics and business is relatively low compared to those without such qualifications. Additionally, the majority of board members are Indonesian citizens.